Composite flame-retardant coating and preparation method thereof as well as flame-retardant aerogel coating and preparation method thereof

By preparing composite flame retardant coatings, combined with multi-layer structure design of polyacrylic resin, composite aerogel and glass microbeads, the problem of insufficient adhesion and fire resistance of aerogel coatings is solved, and high adhesion and excellent flame retardant and heat insulation are achieved, which is suitable for a variety of industrial applications.

CN119662073AInactive Publication Date: 2025-03-21CHINA UNIV OF PETROLEUM (BEIJING)
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411602919.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The lack of adhesion and fire resistance of existing aerogel coatings limits their use in industrial applications.

Method used

By performing polymerization reaction in the presence of an initiator and water, a polyacrylic resin is prepared, and a first contact mixing and drying is performed in water, a composite aerogel is prepared, and then the polyacrylic resin, composite aerogel and glass microbeads are mixed in the second contact to prepare a composite flame retardant coating with high adhesion and excellent flame retardant and heat insulation effect is prepared.

Benefits of technology

It significantly improves the flame retardant and smoke suppressing properties of the substrate, and can be used in thermal insulation, oil and gas production, transportation, and has a simple process and is easy to commercially produce.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119662073A_ABST
    Figure CN119662073A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of new materials, and discloses a composite flame-retardant coating and a preparation method thereof, and a flame-retardant aerogel coating and a preparation method thereof. The method comprises the following steps: (1) in the presence of an initiator and water I, carrying out polymerization reaction on a sulfonate monomer containing double bonds, a phosphate monomer containing double bonds and a hydroxyethyl acrylate monomer to obtain polyacrylic resin; in the presence of water II, black phosphorus, inorganic fibers and the inorganic sol are sequentially subjected to first contact mixing and drying, and composite aerogel is obtained; and (2) carrying out second contact mixing on the polyacrylic resin, the composite aerogel and glass beads to obtain the composite flame-retardant coating. The composite flame-retardant coating prepared through the method for preparing the composite flame-retardant coating has high adhesive force, a flame-retardant gel coating obtained by applying the composite flame-retardant coating to the surface of rigid polyurethane foam has excellent flame-retardant and heat-insulating effects, and the flame-retardant performance and smoke suppression performance of the rigid polyurethane foam can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of new materials, and in particular to a composite flame retardant coating and a preparation method thereof, a flame retardant gas gel coating and a preparation method thereof. Background Art

[0002] Widely used in industrial scenarios, rigid polyurethane foam (RPUF) as an insulation material has the characteristics of high cross-linking degree, three-dimensional structure, and almost closed cells. It has good mechanical strength, ultra-low thermal conductivity, excellent corrosion resistance and low density. However, RPUF has a limiting oxygen index of about 19%, is extremely flammable, and has a great potential fire hazard; at the same time, RPUF will decompose and release a large amount of toxic gases in a fire, which may cause serious fire accidents. The fire-retardant coating on the surface of the foam can protect the underlying matrix from thermal degradation and suppress the spread of fire without compromising its inherent mechanical properties. This is considered to be a promising environmentally friendly strategy to give the material high performance.

[0003] Aerogel coating is an emerging alternative material that can be flexibly applied to prefabricated insulation products. Generally, fire resistance and thermal properties can be improved by increasing the content of inorganic fillers such as aerogel. For example, CN 113402762A discloses a method for preparing a heat-insulating flame-retardant polyurethane-silicon aerogel composite insulation material, which is a method for preparing a phosphorus-containing flame-retardant component using 2-hydroxyethyl acrylate and diphenyl chlorophosphate, and the phosphorus-containing flame-retardant component and ethyl orthosilicate are used as a composite silicon source to prepare a flame-retardant filler, and the flame-retardant filler and dimethyl methyl phosphate are foamed to prepare a composite insulation material. This scheme utilizes the excellent thermal insulation and flame-retardant properties of silicon aerogel, and the principle of synergistic flame retardancy with dimethyl methyl phosphate, but the aerogel coating has insufficient adhesion and leads to a delamination problem, which seriously limits its application.

[0004] Some studies have used freeze-drying technology to coat the outside of RPUF with an aerogel coating, giving RPUF excellent flame retardant and smoke suppression properties. However, freeze-drying technology is difficult to produce commercial RPUF products.

[0005] Therefore, careful consideration of component selection and processing techniques is urgently needed to develop ideal aerogel coatings. Summary of the invention

[0006] The purpose of the present invention is to solve the problem of insufficient adhesion and fire resistance of aerogel coatings in the prior art.

[0007] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a composite flame retardant coating, the method comprising:

[0008] (1) in the presence of an initiator and water I, polymerizing a sulfonate monomer containing a double bond, a phosphate monomer containing a double bond, and a hydroxyethyl acrylate monomer to obtain a polyacrylic acid resin; and

[0009] In the presence of water II, black phosphorus, inorganic fibers and inorganic sol are sequentially subjected to first contact mixing and drying to obtain a composite aerogel;

[0010] (2) subjecting the polyacrylic acid resin, the composite aerogel and the glass microspheres to a second contact mixing to obtain the composite flame retardant coating;

[0011] Wherein, in step (1), the molar ratio of the double-bond-containing sulfonate monomer, the double-bond-containing phosphate monomer and the hydroxyethyl acrylate monomer is 1:0.8-1:0.5-1;

[0012] In step (2), the particle size D of the glass microspheres is 90 10-30μm, bulk density 0.25-0.35t / m 3 .

[0013] The second aspect of the present invention provides a composite flame retardant coating prepared by the method described in the first aspect.

[0014] The third aspect of the present invention provides a flame retardant gas gel coating, which comprises a substrate and a composite flame retardant coating applied to the upper and lower surfaces of the substrate;

[0015] The composite flame retardant coating is the composite flame retardant coating described in the second aspect.

[0016] The fourth aspect of the present invention provides a method for preparing the flame retardant gas gel coating of the third aspect, the method comprising: applying a composite flame retardant coating to the upper and lower surfaces of a substrate, and drying to obtain the flame retardant gas gel coating.

[0017] Through the above technical solution, the present invention has at least the following advantages:

[0018] (1) The method for preparing a composite flame retardant coating provided by the present invention introduces sulfonic acid groups, phosphate groups and hydroxyl groups into the molecular chain of polyacrylic resin through molecular structural design, thereby enhancing the interfacial interaction with the substrate and having high adhesion; and combining the heat insulation and flame retardant effect of aerogel powder, it is mixed with hollow glass microspheres to prepare a fire-safe composite flame retardant coating with excellent flame retardant and heat insulation effects and high adhesion; the composite flame retardant coating is applied to the surface of the substrate to significantly improve the flame retardant and smoke suppression properties of the substrate, and can be used in thermal insulation, oil and gas production, and transportation fields.

[0019] (2) The method for preparing the composite flame-retardant coating provided by the present invention can be dried in a variety of ways, has a simple process, and can solve the problem of complex aerogel production process in aerogel flame-retardant coatings.

[0020] (3) The composite flame retardant coating provided by the present invention has the advantages of fire resistance, high temperature resistance, and better adhesion performance. When applied to the surface of a substrate as a flame retardant gas gel coating, it can significantly improve the fire safety of the substrate.

[0021] (4) The flame retardant gas gel coating provided by the present invention can form a carbon layer during the combustion pyrolysis process to inhibit heat transfer and protect the rigid polyurethane foam matrix. It has significant flame retardant, fireproof and heat insulating properties and has an excellent smoke suppression effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is an adhesion curve diagram of the composite flame retardant coating prepared in Example 1 of the present invention applied to different substrates;

[0023] Figure 2 is a graph showing the adhesion strength of the composite flame retardant coating prepared in Example 1 of the present invention when applied to different substrates;

[0024] Figure 3 It is a heat release rate curve diagram of the flame retardant gas gel coating prepared by the composite flame retardant coating of Examples 1-4 of the present invention and the untreated pure rigid polyurethane foam;

[0025] Figure 4 It is a total heat release curve of the flame retardant gas gel coating prepared by the composite flame retardant coating of Examples 1-4 of the present invention and the untreated pure rigid polyurethane foam;

[0026] Figure 5 It is a total smoke production curve of the flame retardant gas gel coating prepared from the composite flame retardant coating of Examples 1-4 of the present invention and the untreated pure rigid polyurethane foam;

[0027] Figure 6 It is a carbon monoxide production curve of the flame retardant gas gel coating prepared by the composite flame retardant coating of Examples 1-4 of the present invention and the untreated pure rigid polyurethane foam;

[0028] Figure 7 It is a data chart of oxygen index and UL-94 grade of flame retardant gas gel coating prepared from composite flame retardant coating of Examples 1-4 of the present invention and untreated pure rigid polyurethane foam. DETAILED DESCRIPTION

[0029] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0030] In the present invention, the normal temperature refers to a temperature of 22±2°C.

[0031] As mentioned above, the first aspect of the present invention provides a method for preparing a composite flame retardant coating, the method comprising:

[0032] (1) in the presence of an initiator and water I, polymerizing a sulfonate monomer containing a double bond, a phosphate monomer containing a double bond, and a hydroxyethyl acrylate monomer to obtain a polyacrylic acid resin; and

[0033] In the presence of water II, black phosphorus, inorganic fibers and inorganic sol are sequentially subjected to first contact mixing and drying to obtain a composite aerogel;

[0034] (2) subjecting the polyacrylic acid resin, the composite aerogel and the glass microspheres to a second contact mixing to obtain the composite flame retardant coating;

[0035] Wherein, in step (1), the molar ratio of the double-bond-containing sulfonate monomer, the double-bond-containing phosphate monomer and the hydroxyethyl acrylate monomer is 1:0.8-1:0.5-1;

[0036] In step (2), the particle size D of the glass microspheres is 90 10-30μm, bulk density 0.25-0.35t / m 3 .

[0037] It should be noted that, in the present invention, D 90 It refers to the particle size corresponding to 90% of the cumulative particle size distribution of glass microspheres measured by Malvern 2000 laser particle size analyzer, that is, 90% of the particles have a particle size smaller than this particle size.

[0038] Preferably, in step (1), the double bond-containing sulfonate monomer is selected from at least one of sodium vinyl sulfonate, sodium allyl sulfonate, sodium styrene sulfonate, potassium vinyl sulfonate, potassium salt of 3-sulfopropyl methacrylate and 2-acrylamide-2-methylpropane sulfonic acid, preferably at least one of sodium vinyl sulfonate, sodium allyl sulfonate and 2-acrylamide-2-methylpropane sulfonic acid. The inventors have found that in this preferred case, the flame retardant and smoke suppression properties of the flame retardant gas gel coating obtained by the technical solution provided by the present invention are more superior.

[0039] Preferably, in step (1), the double bond-containing phosphate monomer is selected from 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate, triallyl phosphate, di[2-(methacryloyloxy)ethyl]phosphate, acrylic acid phosphate FM30 and acrylic phosphate At least one of FM20 is preferably at least one of 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate, triallyl phosphate and di[2-(methacryloyloxy)ethyl] phosphate. In this preferred case, the flame retardant and smoke suppression properties of the flame retardant gas gel coating obtained by the technical solution provided by the present invention are more superior.

[0040] Preferably, in step (1), the weight ratio of the double-bond-containing sulfonate monomer, the initiator and the water I is 0.05-0.1:0.001-0.005:1, preferably 0.05-0.06:0.003-0.004:1.

[0041] Preferably, the weight ratio of the black phosphorus, the inorganic fiber and the inorganic sol is 1:0.5:1-5, preferably 1:0.5:1-2.5.

[0042] Preferably, the weight ratio of the black phosphorus to the water II is 1:1-10, preferably 1:4-9.

[0043] Preferably, in step (2), the weight ratio of the polyacrylic resin, the composite aerogel and the glass microspheres is 1-10:1:0.5, preferably 5-9:1:0.5. In this preferred embodiment, the technical solution provided by the present invention can obtain a flame retardant gas gel coating with better flame retardant and smoke suppression performance.

[0044] Preferably, based on the total weight of the glass microspheres, the content of SiO2 in the glass microspheres is 20-30wt%, and the content of CaO is 1-3wt%.

[0045] Preferably, the compressive strength of the glass microspheres is 100-220 MPa.

[0046] Preferably, the inorganic fiber is selected from at least one of silica fiber, alumina fiber, mullite fiber and SiC fiber, preferably at least one of silica fiber, alumina fiber and mullite fiber.

[0047] Preferably, the inorganic sol is selected from at least one of silica sol, alumina sol and zirconia sol, preferably silica sol and / or zirconia sol.

[0048] Preferably, the initiator is selected from at least one of ammonium persulfate, potassium persulfate, azobisisobutyronitrile and dibenzamide peroxide, preferably ammonium persulfate and / or potassium persulfate.

[0049] The present invention has no particular limitation on the specific equipment for the polymerization reaction in step (1). The specific equipment for the polymerization reaction is exemplarily provided in the following text of the present invention, which should not be construed as a limitation on the present invention by those skilled in the art.

[0050] Preferably, in step (1), the polymerization reaction conditions include: temperature of 20-120° C., and time of 5-30 h.

[0051] Preferably, in step (1), the drying method is at least one of room temperature drying, heating drying and freeze drying.

[0052] It should be noted that the temperatures of the first contact and mixing and the second contact and mixing are both room temperature.

[0053] According to a preferred specific embodiment, the method further comprises: in step (1), grinding and sieving the product obtained by drying to obtain the composite aerogel; more preferably, using a Chinese sieve to perform the sieving and taking the sieve, and the sieve hole size of the sieving is 200-800 mesh.

[0054] As mentioned above, the second aspect of the present invention provides a composite flame retardant coating prepared by the method described in the first aspect.

[0055] As mentioned above, the third aspect of the present invention provides a flame retardant gas gel coating, which comprises a substrate and a composite flame retardant coating applied to the upper and lower surfaces of the substrate;

[0056] The composite flame retardant coating is the composite flame retardant coating described in the second aspect.

[0057] As mentioned above, the fourth aspect of the present invention provides a method for preparing the flame retardant gas gel coating described in the third aspect, the method comprising: applying the composite flame retardant coating to the upper and lower surfaces of the substrate, and drying to obtain the flame retardant gas gel coating.

[0058] Preferably, the coating thickness is independently 0.1-5 mm / surface.

[0059] Preferably, the substrate is rigid polyurethane foam.

[0060] Preferably, the coating method is selected from at least one of a brush coating method, a spray coating method and a dip coating method.

[0061] Preferably, the drying treatment conditions include: temperature of 20-80° C. and time of 5-24 h.

[0062] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the drugs and reagents used are all commercially available.

[0063] Sodium vinyl sulfonate was purchased from Beijing Bailingwei Technology Co., Ltd., CAS No.: 3039-83-6.

[0064] Sodium allyl sulfonate was purchased from Shanghai Myrel Biochemical Technology Co., Ltd., CAS No.: 2495-39-8.

[0065] 2-Methyl-2-acrylic acid-2-hydroxyethyl ester phosphate was purchased from Beijing Xinbaohai Chemical Technology Co., Ltd., CAS No.: 52628-03-2.

[0066] Triallyl phosphate was purchased from Shanghai Jizhi Biochemical Technology Co., Ltd., CAS No.: 1623-19-4.

[0067] Di[2-(methacryloyloxy)ethyl]phosphate was purchased from Hubei Jusheng Technology Co., Ltd., CAS No.: 32435-46-4.

[0068] Hydroxyethyl acrylate was purchased from Guangzhou Yuanda New Materials Co., Ltd., CAS No.: 818-61-1.

[0069] Glass beads (B-1): particle size D 90 10μm, bulk density 0.35t / m 3 , the compressive strength is 207MPa.

[0070] Glass beads (B-2): particle size D 90 30μm, bulk density 0.25t / m 3 , the compressive strength is 110MPa.

[0071] Glass beads (B-3): particle size D 90 The particle size is 85 μm and the bulk density is 0.14 t / m 3 , the compressive strength is 10MPa.

[0072] In the following examples, acrylic acid phosphate FM30 is a mixture of acrylic acid monophosphate and acrylic acid diphosphate, the phosphate monomer is synthesized from O-(EO)n>10-CH3, and the active acrylic acid group is methacrylate; it was purchased from Beijing Baiyuan Chemical Co., Ltd.

[0073] The following examples are used to illustrate the method for preparing the composite flame retardant coating of the present invention.

[0074] Example 1

[0075] (1) in the presence of an initiator and water I and under stirring at room temperature, a sulfonate monomer containing a double bond, a phosphate monomer containing a double bond and a hydroxyethyl acrylate monomer are added to a 250 mL three-necked flask equipped with a constant pressure dropping funnel, a reflux condenser, a mechanical stirrer and a nitrogen inlet, and mixed evenly, and then the above device is transferred to an oil bath pot and heated to perform a polymerization reaction to obtain a polyacrylic acid resin; and

[0076] At room temperature, in the presence of water II, black phosphorus, inorganic fibers and inorganic sol are stirred and dispersed to perform first contact mixing to obtain a black phosphorus / inorganic fiber dispersion;

[0077] and drying the black phosphorus / inorganic fiber dispersion to obtain a black phosphorus / inorganic fiber aerogel;

[0078] Then the black phosphorus / inorganic fiber aerogel is ground into powder, sieved with a Chinese sieve and the sieve-surface material is taken to obtain a composite aerogel;

[0079] (2) At room temperature, the polyacrylic acid resin, the composite aerogel and the glass microbeads are stirred uniformly to perform a second contact mixing, and then a composite flame retardant coating is obtained.

[0080] The raw materials, their proportions and reaction conditions of this example are shown in Table 1.

[0081] Examples 2 to 4 are all prepared using the same preparation method as Example 1, except that the raw materials and their ratios, and reaction conditions are different, as shown in Table 1.

[0082] Table 1 (the amount of initiator is 0.15g, the amount of water II is 9g, and the amount of glass microspheres is 1g)

[0083]

[0084]

[0085] Example 5

[0086] This example is carried out in a similar manner to that of Example 1, except that the sulfonate monomer containing a double bond in this example is replaced with 3-sulfonate propyl methacrylate potassium salt to obtain a composite flame retardant coating.

[0087] Example 6

[0088] This example is carried out in a similar manner to Example 1, except that the double-bonded phosphate monomer of this example is replaced with acrylic phosphate. FM30, to obtain a composite flame retardant coating.

[0089] Example 7

[0090] This example is carried out in a similar manner to Example 1, except that the amount of glass microspheres in this example is kept unchanged, and the weight ratio of polyacrylic acid resin, composite aerogel and glass microspheres is adjusted to 12:1:1 to obtain a composite flame retardant coating.

[0091] Comparative Example 1

[0092] This comparative example is carried out in a similar manner to Example 1, except that the amount of the sulfonate monomer containing a double bond in this comparative example is kept unchanged, and the molar ratio of the sulfonate monomer containing a double bond, the phosphate monomer containing a double bond and the hydroxyethyl acrylate monomer is adjusted to 1:0.1:1 to obtain a composite flame retardant coating.

[0093] Comparative Example 2

[0094] This comparative example was carried out in a similar manner to Example 1, except that the amount of glass microbeads in this comparative example was kept unchanged, and the type of glass microbeads was changed to B-3 to obtain a composite flame retardant coating.

[0095] Test Case

[0096] At room temperature, the adhesion and adhesion strength of the composite flame retardant coating prepared in the example were tested when applied to different substrates such as wood, steel, ceramics, glass, polyethylene (PS), nylon (PA), polyvinyl chloride (PVC) and polymethyl methacrylate (PMMA). The peak data of the adhesion test are shown in Table 2, and the results of the adhesion strength test are shown in Table 3.

[0097] Among them, the test method of adhesion and adhesion strength is: according to the ASTM F2255-05 (2015) standard, the material is subjected to a lap shear test, specifically:

[0098] ① Cut the sample into a rectangular specimen of 4 cm (length) × 1.2 cm (width); ② Apply a coating sample with a side length of 1.2 cm and a thickness of 1 mm on the side of the sample surface close to the end point; ③ Place another sample on the coating sample to form a square overlapping area with a side length of 1.2 cm; ④ Perform a tensile test to obtain adhesion and adhesion strength data.

[0099] Table 2

[0100]

[0101] Table 3

[0102]

[0103] The present invention Figure 1 exemplarily provides an adhesion curve diagram of the composite flame retardant coating prepared in Example 1 of the present invention applied to different substrates; Figure 1 It can be seen that the composite flame retardant coating prepared in Example 1 has strong adhesion to substrates such as wood, steel, ceramics, glass, polyethylene (PS), nylon (PA), polyvinyl chloride (PVC) and polymethyl methacrylate (PMMA).

[0104] The present invention Figure 2 exemplarily provides a data graph of the adhesion strength of the composite flame retardant coating prepared in Example 1 of the present invention applied to different substrates; Figure 2 It can be seen that the composite flame retardant coating prepared in Example 1 has strong adhesion strength to substrates such as wood, steel, ceramics, glass, polyethylene (PS), nylon (PA), polyvinyl chloride (PVC) and polymethyl methacrylate (PMMA).

[0105] The following application examples are used to illustrate the method for preparing a flame-retardant gel coating of the present invention.

[0106] Application Example 1

[0107] The composite flame retardant coating prepared in Example 1 was applied to the upper and lower surfaces of the substrate (rigid polyurethane foam) and dried (temperature was 60°C, time was 3h), and the coating thickness was 0.5mm / surface to obtain a flame retardant gas gel coating.

[0108] Application Example 2

[0109] The method of Application Example 1 is followed, except that the composite flame retardant coating prepared in Example 2 is used instead of the composite flame retardant coating prepared in Example 1, and the drying conditions are adjusted to: temperature of 60° C. and time of 5 h.

[0110] Application Example 3

[0111] The method of Application Example 1 is followed, except that the composite flame retardant coating prepared in Example 3 is used instead of the composite flame retardant coating prepared in Example 1, and the drying conditions are adjusted to: temperature of 65° C. and time of 5 h.

[0112] Application Example 4

[0113] The method of Application Example 1 is followed, except that the composite flame retardant coating prepared in Example 4 is used instead of the composite flame retardant coating prepared in Example 1, and the drying conditions are adjusted to: temperature of 60° C. and time of 10 h.

[0114] Application Example 5 to Application Example 7

[0115] The method of Application Example 1 is followed, except that the composite flame retardant coatings prepared in Examples 5 to 7 are used to replace the composite flame retardant coating prepared in Example 1.

[0116] Gas-resistant gel coatings were obtained respectively.

[0117] Comparative Application Example 1 to Comparative Application Example 2

[0118] The method of Application Example 1 is followed, except that the composite flame retardant coatings prepared in Comparative Examples 1 and 2 are used to replace the composite flame retardant coating prepared in Example 1.

[0119] Gas-resistant gel coatings were obtained respectively.

[0120] Application test case

[0121] The flame-retardant gel coating prepared in the corresponding example was subjected to performance tests, including heat release rate, total heat release, total smoke production, carbon monoxide production, oxygen index and UL-94 grade, and the above test results were compared with the test results of untreated pure rigid polyurethane foam. The test results are shown in Table 4.

[0122] Among them, the relevant test methods are as follows:

[0123] Heat release rate, total smoke production, and carbon monoxide production: According to ASTM E1354 / ISO 5660, the combustion performance of the material was tested and evaluated using a cone calorimeter (Fire Testing Technology, UK). The standard sample of the material (100×100×3mm 3 ) is wrapped in aluminum foil and placed on the sample stage of the calorimeter for combustion testing. The radiation flux is usually set to 35kW / m 2 .

[0124] Oxygen index and UL-94 level: The limiting oxygen index (LOl) is measured by HC-2 oxygen index meter (Jiangning Analytical Instrument Factory), the sample size is 100mm×6.5mm×3.2mm, and the test standard is based on standard ASTM D2863. The vertical combustion test (UL-94) is carried out on CFZ-2 horizontal vertical combustion tester (Jiangning Analytical Instrument Factory), the sample size is 130.0mm×13.0mm×3.2mm, 130.0mm×13.0mm×1.6mm, and the test standard is based on standard ASTM D3801.

[0125] Table 4

[0126]

[0127] The present invention Figure 3 illustratively provides heat release rate curves of flame retardant gas gel coatings prepared from composite flame retardant coatings of Examples 1 to 4 of the present invention and untreated pure rigid polyurethane foam, wherein pure foam refers to pure rigid polyurethane foam; Figure 3It can be seen that the peak heat release rate of the flame-retardant gas gel coating prepared in Example 1-4 is 200-300 kW / m 2 The peak heat release rate of untreated pure rigid polyurethane foam is between 400-500kW / m 2 This indicates that the flame retardant gas gel coating provided by the present invention exhibits good flame retardant properties.

[0128] The present invention Figure 4 The total heat release curves of the flame retardant gas gel coating prepared by the composite flame retardant coating of Examples 1 to 4 of the present invention and the untreated pure rigid polyurethane foam are provided as examples, wherein the pure foam refers to the pure rigid polyurethane foam; Figure 4 It can be seen that the total heat release value of the flame-retardant gel coating prepared in Example 1-4 is 40-50 MJ / m 2 The total heat release value of untreated pure rigid polyurethane foam exceeds 55MJ / m 2 This indicates that the flame retardant gas gel coating prepared in the present invention exhibits good flame retardant properties.

[0129] The present invention Figure 5 , a total smoke production curve of the flame retardant gas gel coating prepared by the composite flame retardant coating of Examples 1 to 4 of the present invention and the untreated pure rigid polyurethane foam is provided by way of example, wherein the pure foam refers to the pure rigid polyurethane foam; Figure 5 It can be seen that the total smoke generation of the flame-retardant gel coating prepared in Example 1-4 is 3-4m 2 The total smoke generation of untreated pure rigid polyurethane foam exceeds 7m 2 This indicates that the flame-retardant gel coating provided by the present invention exhibits good smoke suppression performance.

[0130] The present invention Figure 6 exemplarily provides a carbon monoxide production curve of the flame retardant gas gel coating prepared by the composite flame retardant coating of Examples 1-4 of the present invention and the untreated pure rigid polyurethane foam, wherein the pure foam refers to the pure rigid polyurethane foam; Figure 6 It can be seen that the carbon monoxide production of the flame retardant gel coatings prepared in Examples 1-4 is between 2-5 mg / s, while the carbon monoxide production of pure rigid polyurethane foam exceeds nearly 9 mg / s. This shows that the flame retardant gel coating provided by the present invention exhibits good smoke suppression and toxicity reduction performance.

[0131] The present invention Figure 7 illustratively provides oxygen index and UL-94 grade data of flame retardant gas gel coatings prepared from composite flame retardant coatings of Examples 1-4 of the present invention and untreated pure rigid polyurethane foam, wherein pure foam refers to pure rigid polyurethane foam; Figure 7It can be seen that the flame retardant and gas gel coatings prepared in Application Examples 1-4 all reach the UL-94 V0 level, and the oxygen index is about 40%, while the pure rigid polyurethane foam has no level in the UL-94 test, and the oxygen index does not exceed 20%. This shows that the flame retardant and gas gel coating provided by the present invention exhibits good flame retardant and smoke suppression performance.

[0132] It can be seen from the above results that the composite flame retardant coating prepared by the method for preparing a composite flame retardant coating provided by the present invention has high adhesion, and the flame retardant gas gel coating obtained by applying the composite flame retardant coating to the surface of rigid polyurethane foam has excellent flame retardant and heat-insulating effects, and can significantly improve the flame retardant and smoke suppression properties of rigid polyurethane foam, thereby being applicable to thermal insulation, oil and gas production, and transportation fields.

[0133] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a composite flame retardant coating, characterized in that: The method includes: (1) in the presence of an initiator and water I, polymerizing a sulfonate monomer containing a double bond, a phosphate monomer containing a double bond, and a hydroxyethyl acrylate monomer to obtain a polyacrylic acid resin; and In the presence of water II, black phosphorus, inorganic fibers and inorganic sol are sequentially subjected to first contact mixing and drying to obtain a composite aerogel; (2) subjecting the polyacrylic acid resin, the composite aerogel and the glass microspheres to a second contact mixing to obtain the composite flame retardant coating; Wherein, in step (1), the molar ratio of the double-bond-containing sulfonate monomer, the double-bond-containing phosphate monomer and the hydroxyethyl acrylate monomer is 1:0.8-1:0.5-1; In step (2), the particle size D of the glass microspheres is 90 10-30μm, bulk density 0.25-0.35t / m 3 .

2. The method according to claim 1, wherein: In step (1), the double bond-containing sulfonate monomer is selected from at least one of sodium vinyl sulfonate, sodium allyl sulfonate, sodium styrene sulfonate, potassium vinyl sulfonate, potassium methacrylate 3-sulfonate propyl ester and 2-acrylamido-2-methylpropane sulfonic acid.

3. The method according to claim 1, wherein: In step (1), the double bond-containing phosphate monomer is selected from 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate, triallyl phosphate, di[2-(methacryloyloxy)ethyl]phosphate, acrylic acid phosphate FM30 and acrylic phosphate At least one of FM20.

4. The method according to any one of claims 1 to 3, wherein: In step (1), the weight ratio of the double-bond-containing sulfonate monomer, the initiator and the water I is 0.05-0.1:0.001-0.005:1; And / or, the weight ratio of the black phosphorus, the inorganic fiber and the inorganic sol is 1:0.5:1-5; And / or, the weight ratio of the black phosphorus to the water II is 1:1-10; And / or, in step (2), the weight ratio of the polyacrylic resin, the composite aerogel and the glass microspheres is 1-10:1:0.

5.

5. The method according to any one of claims 1 to 3, wherein: The inorganic fiber is selected from at least one of silica fiber, alumina fiber, mullite fiber and SiC fiber; And / or, the inorganic sol is selected from at least one of silica sol, alumina sol and zirconia sol; And / or, the initiator is selected from at least one of ammonium persulfate, potassium persulfate, azobisisobutyronitrile and dibenzamide peroxide.

6. A composite flame retardant coating prepared by the method according to any one of claims 1 to 5.

7. A flame-retardant gel coating, characterized in that: The flame retardant gas gel coating comprises a substrate and a composite flame retardant coating applied on the upper and lower surfaces of the substrate; The composite flame retardant coating is the composite flame retardant coating according to claim 6.

8. A method for preparing the flame-retardant gas gel coating according to claim 7, characterized in that: The method comprises: coating the composite flame retardant coating on the upper and lower surfaces of the substrate, and performing drying treatment to obtain the flame retardant gas gel coating.

9. The method according to claim 8, wherein: The coating thickness is independently 0.1-5 mm / surface; And / or, the substrate is rigid polyurethane foam.

10. The method according to claim 8 or 9, wherein: The coating method is selected from at least one of a brush coating method, a spray coating method and a dip coating method; And / or, the drying treatment conditions include: temperature of 20-80° C. and time of 5-24 h.

Citation Information

Patent Citations

  • Preparation method of thermal-insulation flame-retardant polyurethane-silica aerogel composite thermal insulation material

    CN113402762A